“In the army I’m no longer typecast as the son of migrant workers”: modalities of inclusion and belonging among children of migrant workers in the military in Israel - Sabar, Galia; Babis, Deby; Lifszyc-Friedlander, Anabel; Ben-Shalom, Uzi (Frontiers in Psychology, 2024)
This article explores how non-citizen minorities experience military service, focusing on children of international labor migrants who served in the Israel Defense Forces. During the 1990’s, Israel witnessed an influx of migrant workers, primarily from the Philippines, Latin America and Africa. However, due to Israeli immigration policies, neither they nor their Israeli-born children were eligible for citizenship. Consequently, upon reaching the age of 18, unlike their Israeli peers, these children were not recruited into the army. Furthermore, they lived under constant threat of deportation. Due to advocacy by civil society organizations, in 2006 and 2010 the government granted civic status (permanent residency) to approximately 1,500 children. This made them eligible for military service, a somewhat unique situation globally. Upon completion of their first year of military service, they were eligible for Israeli citizenship and their immediate family members were eligible for permanent residency. Through qualitative and quantitative research, we examine inclusion and belonging amongst children of migrant workers who served in the military. Our findings suggest that military service enabled them to overcome the exclusionary boundaries they experienced as children in three ways. Firstly, they achieved formal belonging by receiving citizenship. Secondly, they achieved informal belonging through the cultural and social capital this service accrued within Israeli society. Finally, for some, military service deepened their knowledge of Judaism and, in certain cases, led to conversion, thus fostering religious belonging. These three aspects facilitated inclusion and a sense of belonging for these formerly marginalized children while also enhancing their legitimacy within Israeli society. This unique case study contributes to ongoing global debates about the experiences of minority groups in the military.